Analysis of gene expression profile of peripheral blood in alveolar and cystic echinococcosis - Liu, Lei; Chen, Fan; Jiang, Shan; Zhong, Bo; Li, Wei; Xu, Kejun; Wang, Qi; Wang, Ying; Cao, Jianping (Frontiers in Cellular and Infection Microbiology, 2022)
RNA-sequencing (RNA-seq) is a versatile, high-throughput technology that is being widely employed for screening differentially expressed genes (DEGs) in various diseases. Echinococcosis, a globally distributed zoonosis, has been reported to impose a heavy disease burden in pastoral areas of China. Herein we aimed to explore the molecular mechanisms underlying echinococcosis. In this study, peripheral blood samples were collected from six patients with alveolar echinococcosis (AE), six patients with cystic echinococcosis (CE), and six healthy controls. RNA-Seq (mRNA) was performed to detect gene transcript and expression levels, and DEGs were subjected to bioinformatic analyses. In comparison with healthy controls, 492 DEGs (270 upregulated, 222 downregulated) were found in the AE group and 424 DEGs (170 upregulated, 254 downregulated) were found in the CE group (|log2 (fold change)| > 1 and P < 0.05). Further, 60 genes were upregulated and 39 were downregulated in both the AE and CE groups. Gene ontology enrichment analysis indicated that DEGs were mainly involved in molecular functions, including extracellular space, extracellular region, organ and system development, and anatomical structure development. Protein–protein interaction (PPI) networks were constructed to depict the complex relationship between DEGs and interacting proteins.